Impact of leadership and employee engagement on job satisfaction: a case study of a private international University in Malaysia - Tang, Yvonne Yee Wen (2019)
This MBA management project includes a case study that was carried out to establish the influence of leadership and employee engagement on the job satisfaction in a private international University in Malaysia. Leadership plays a vital role in ensuring employee engagement and job satisfaction. As the selected organisation has experienced multiple changes in the management level over the recent years, this high turnover rate has become rather concerning and is the main motivation behind this research study. The research objectives is to establish the relationship between leadership and job satisfaction, leadership and employee engagement, as well as employee engagement and job satisfaction. In order to ensure that an exact, systematic sampling method was applied in this study, the researcher used purposive target sampling as a form of non-probability sampling which involves a cross sectional design at a single time point. The researcher designed an electronic survey questionnaire specifically for this study to discover detailed data in regards to the opinions, perceptions and understanding of the research variables from the University’s employees. The electronic questionnaire was disseminated by means of a group email to the identified participants which formed part of the selected organisation. There was a total of 53 responses received electronically and all 53 were usable, representing a substantial response rate. The statistical findings from the research survey defined leadership and employee engagement in terms of job satisfaction. The results showed that there are transformational and transactional leadership styles present at the University. The results also show that laissez-faire leadership style is not being practised at the University. Based on the study’s findings, there is significant evidence to support that there is a positive relationship between transformational leadership and job satisfaction. Additionally, the findings also show that there is a positive relationship between transactional leadership and job satisfaction. On the other hand, there is also clearly indication that there is a negative relationship between laissez-faire leadership and job satisfaction. Therefore, it can be deduced that leadership does have a positive or negative relationship with job satisfaction and employee engagement will positively impact job satisfaction. As the research shows that leadership and employee engagement does influence the employees’ job satisfaction levels, it is imperative for the University to focus strongly on these two specific variables to make sure that the employees are satisfied with their jobs. It is important for the organisation to equip their leaders properly through leadership development and training programs to make sure their leaders have the required knowledge and skills to motivate their subordinates. Research shows that the term employee engagement is not well understood and the University needs to make sure that the employees clearly understand the term and what it encompasses. Awareness campaigns can be introduced to promote an engaged culture in the organisation’s employees. This research study could positively contribute to the selected organisation and its employees, as well as future research on this particular area.